ADAMDEC1 accelerates GBM progression via activation of the MMP2-related pathway - Qi, Huimin; Wang, Ping; Sun, Hongliang; Li, Xiaohan; Hao, Xinwei; Tian, Wenxiu; Yu, Liting; Tang, Jiajian; Dong, Junhong; Wang, Hongmei (Frontiers in Oncology, 2022)
The ADAM (a disintegrin and metalloprotease) gene-related family including ADAM, ADAMTS, and ADAM-like decysin-1 has been reported to play an important role in the pathogenesis of multiple diseases, including cancers (lung cancer, gliomas, colorectal cancer, and gastrointestinal cancer). However, its biological role in gliomas remains largely unknown. Here, we aimed to investigate the biological functions and potential mechanism of ADAMDEC1 in gliomas. The mRNA and protein expression levels of ADAMDEC1 were upregulated in glioma tissues and cell lines. ADAMDEC1 showed a phenomenon of “abundance and disappear” expression in gliomas and normal tissues in that the higher the expression of ADAMDEC1 presented, the higher the malignancy of gliomas and the worse the prognosis. High expression of ADAMDEC1 was associated with immune response. Knockdown of ADAMDEC1 could decrease the proliferation and colony-forming ability of LN229 cells, whereas ADAMDEC1 overexpression has opposite effects in LN229 cells in vitro. Furthermore, we identified that ADAMDEC1 accelerates GBM progression via the activation of the MMP2 pathway. In the present study, we found that the expression levels of ADAMDEC1 were significantly elevated compared with other ADAMs by analyzing the expression levels of ADAM family proteins in gliomas. This suggests that ADAMDEC1 has potential as a glioma clinical marker and immunotherapy target.